Digital Storytelling for Improving ESP’s Students’ Motivation and Autonomy During Covid-19 Pandemic: A Conceptual Paper - Reza Anggriyashati Adara (Journal of English Teaching and Linguistics Studies (JET Li), 2022)
Covid-19 pandemic has changed the way ESP (English for Specific Purposes) teachers and students interact in the classrooms. As teachers and students need to use online method to teach and learn English, an alternative strategy is needed to maintain students’ motivation and autonomy. One of alternatives which can be taken by teachers to improve students’ motivation and autonomy is digital storytelling. It is because digital storytelling has been considered effective to improve students’ motivation and autonomy. Therefore, the present study is a conceptual paper which will discuss the possibilities of digital storytelling integration to ESP classes. In addition, the present study aims to discuss strategies that can be taken to apply digital storytelling to ESP classrooms.